Ефективність використання червоного шламу при розробці кислотостійких гібридних лужних цементів - Zozulynets, V.; Kovalchuk, O. (Ways to Improve Construction Efficiency, 2023)
The use of secondary industrial products has long been an integral part of the construction industry. The most common man-made raw materials used in the production of building materials, in addition to slag, are fly ash and red mud. This work is devoted to the study of the effectiveness of using red mud as an additional source of an alumina silicate component of man-made origin in the production of alkali-activated cements with increased acid resistance. In conventional cement systems, the use of significant amounts of red mud is not possible due to the high content of alkali metal compounds and heavy elements, but this is not a problem for alkali-activated binders. Red mud obtained by processing bauxite ore using the Bayer process is highly alkaline, and its disposal and reusability are hampered by high sodium concentrations and high pH. That is why, according to the analysis of literature sources, research on the integrated use of red mud is mainly found in only a few areas, among which construction occupies a leading position. In the course of research, the parameters of dough of normal density, hardening terms and strength for the developed systems were determined. Direct determination of the acid resistance index was also carried out using two methods: accelerated and by long-term aging of samples. In this way, the main physical and mechanical characteristics of the developed compounds were determined and the results were analyzed. The obtained results of the study confirmed the possibility of partially replacing alumina silicate components with red mud to obtain acid-resistant alkaline cements. It was found that the introduction of up to 30% of red mud makes it possible to obtain material with an acid resistance coefficient (Ks) in the range of 0.8-0.95.